2001
DOI: 10.1046/j.1464-5491.2001.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of isolated small nerve fibre dysfunction on microvascular control in patients with diabetes mellitus

Abstract: Our study confirms an association between small nerve fibre injury and skin microvascular dysfunction. It further underlines the concept of neurovascular disturbances in the pathogenesis of neurotrophic foot ulceration. Diabet. Med. 18, 489-494 (2001)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 44 publications
2
10
0
4
Order By: Relevance
“…Similar results were observed during thermal hyperemia at 44 8C. Lower microvascular reactivity was found in the whole cohort of diabetic patients (Stansberry et al, 1997), whereas in other studies only in diabetic patients with neuropathy (Stevens et al, 1991;Young et al, 1996) or in those with isolated small nerve fiber dysfunction (Pfutzner et al, 2001). In diabetic patients with neuropathy flow, motion amplitude was reduced (Benbow et al, 1995).…”
Section: Discussionsupporting
confidence: 81%
“…Similar results were observed during thermal hyperemia at 44 8C. Lower microvascular reactivity was found in the whole cohort of diabetic patients (Stansberry et al, 1997), whereas in other studies only in diabetic patients with neuropathy (Stevens et al, 1991;Young et al, 1996) or in those with isolated small nerve fiber dysfunction (Pfutzner et al, 2001). In diabetic patients with neuropathy flow, motion amplitude was reduced (Benbow et al, 1995).…”
Section: Discussionsupporting
confidence: 81%
“…Characterizing these changes may be of particular importance for two reasons. First, it could provide a novel approach for the detection of early neuropathy, since small unmyelinated fibers specifically play an important role in thermoregulation (7,8) and are often the earliest nerve fibers affected in diabetic polyneuropathy (9). In addition, disruptions in normal temperature control may be central to the development of neuropathic pain and sleep disturbance, because neuronal activity itself is highly temperature sensitive (10) and distal extremity warming is critical to sleep onset and maintenance (1113).…”
mentioning
confidence: 99%
“…Prior pharmacokinetics studies showed after TDS application, serum concentrations of estradiol increase rapidly and reach maximal or near maximal values within 24 hours [2,6]. Percutaneous absorption is known to vary due to different factors such as skin thickness, blood flow, lipid content, and number of hair follicles [8].…”
Section: Discussionmentioning
confidence: 99%